2020
DOI: 10.1042/cs20191086
|View full text |Cite
|
Sign up to set email alerts
|

Increased P2X7 expression in the gastrointestinal tract and skin in a humanised mouse model of graft-versus-host disease

Abstract: Background: Allogeneic haematopoietic stem cell transplantation (HSCT) is a curative therapy for blood cancers; but results in the development of graft-versus-host disease (GVHD) in up to 70% of recipients. During GVHD, tissue damage results in ATP release into the extracellular compartment activating P2X7 on antigen-presenting cells, leading to the release of pro-inflammatory cytokines and subsequent activation of donor T cells. Therefore, the aim of the present study was to examine murine (m) P2rx7 and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…Human blood was acquired and used as approved by the University of Wollongong (Wollongong, Australia) Human Ethics Research Committee. Human peripheral blood mononuclear cells (hPBMCs) were isolated as previously described (20) . Briefly, whole blood was collected from healthy human donors (n = 8, aged 23-28 y, 7 male, 1 female), with written informed consent, and separated via density centrifugation with Ficoll-Paque PLUS (GE Healthcare, Uppsala, Sweden).…”
Section: Human Peripheral Blood Mononuclear Cell Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human blood was acquired and used as approved by the University of Wollongong (Wollongong, Australia) Human Ethics Research Committee. Human peripheral blood mononuclear cells (hPBMCs) were isolated as previously described (20) . Briefly, whole blood was collected from healthy human donors (n = 8, aged 23-28 y, 7 male, 1 female), with written informed consent, and separated via density centrifugation with Ficoll-Paque PLUS (GE Healthcare, Uppsala, Sweden).…”
Section: Human Peripheral Blood Mononuclear Cell Isolationmentioning
confidence: 99%
“…All experiments using mice were carried out in the University of Wollongong Rodent Facility as approved by the University of Wollongong Animal Ethics Committee. Female NOD-scid IL2Rγ null (NSG) mice (Australian BioResources, Moss Vale, Australia) were housed and fed as described (20) . NSG mice that had been acclimatised for two weeks (6-7 weeks old) were injected intraperitoneally (i.p.)…”
Section: Humanised Mouse Model Of Gvhdmentioning
confidence: 99%
“…Further complicating an immunosuppressive role for adenosine in this model, is our observation that engraftment of human PBMCs with a polymorphic variant of the ENTPD1 gene, that results in increased CD39 + T regulatory cells, worsens GVHD ( Adhikary et al, 2020 ). Finally, our studies have revealed increased expression of murine P2rx7 and P2rx4 in GVHD tissues from Hu-PBMC-NSG mice compared to those from non-engrafted NSG mice ( Cuthbertson et al, 2020 ) and the presence of functional murine P2X7 receptors in NSG mice ( Geraghty et al, 2017 ), whilst both human P2RX7 and ADORA2 are detected in Hu-PBMC-NSG mice ( Geraghty et al, 2019d ). Collectively, this data suggests Hu-PBMC-NSG mice provide a pre-clinical model of GVHD in which new therapeutics aimed at inhibiting P2X7 receptor activation can be tested, whilst the potential use of this model to test new therapeutics aimed at activating A 2A receptors remains to be established.…”
Section: Purinergic Signaling In Gvhd In Humanized Nsg Micementioning
confidence: 77%
“…injection of 10 × 10 6 human (h) peripheral blood mononuclear cells (PBMCs) into NOD.Cg- Prkdc scid IL2rg tm1Wjl (NSG) mice (Day 0) results in the engraftment of human (h) CD45 + leukocytes predominately hCD4 + and hCD8 + T cells as early as Day 21. The percentages of hCD45 + leukocytes, hCD3 + T cells and hCD4 + or hCD8 + T cells represent the average percentages of these cells among total CD45 + leukocytes, hCD45 + leukocytes and hCD3 + T cells, respectively, typically observed in this model ( Cuthbertson et al, 2020 ). From Week 4, mice display signs of clinical GVHD (as indicated) corresponding with the production of circulating human interferon- γ (hIFN ( γ ), tumor necrosis factor (hTNF) and interleukins (hIL) (as indicated) ( Geraghty et al, 2017 ; Geraghty et al, 2019a ; Geraghty et al, 2019d ), increased murine P2rx7 and P2rx4 expression in GVHD tissues, and histological evidence of GVHD at endpoint (Day 70) ( Cuthbertson et al, 2020 ).…”
Section: Humanized Micementioning
confidence: 98%
“…It will also be interesting to analyze isoform expression in large cohort databases to understand whether they are differentially expressed in MLL-rearranged AML and, in general, in poor outcome patients. Finally, the role of ATP and P2X7 in shaping the bone marrow niche and mediating hematopoietic precursors or leukemic stem cell localization, mobilization, and their behavior following allogeneic transplantation surely deserves further understanding (Salvestrini et al, 2017;Adamiak et al, 2018;Koldej et al, 2018;Cuthbertson et al, 2020;He et al, 2020).…”
Section: P2x7 Role In Leukemiasmentioning
confidence: 99%